A new burst evaluation index of coal–rock combination specimen considering rebound and damage effects of rock. Issue 1 (1st January 2020) - Zhang, Dong-Xiao; Guo, Wei-Yao; Zang, Chuan-Wei; Gong, Xu-Fei; Li, Zhan-Hai; Qiu, Yue; Chen, Wen-guo
Abstract: Obtaining the bursting liability is essential for rock burst mitigation. To reasonably evaluate the bursting liability of coal in deep coal mining, a new modified bursting energy index considering rebound and damage effects of rock is proposed. Then, uniaxial compressive tests of gypsum–rock combination specimens with different rock types are conducted for researching the energy evolution and bursting liability. Third, the traditional bursting energy index K E and modified bursting energy index K ED are compared. At last, the reasonability of K ED is verified through PFC2D simulation. Results show: (1) When evaluating the bursting liability of coal–rock combination, the rebound and damage effects of rock must be considered. (2) The uniaxial compressive strength of gypsum–rock combination specimen nonlinearly increases with increasing rock strength, but the dynamic failure duration exponentially decreases. (3) K E and K ED all increase linearly when the rock strength increases. (4) The slope of fitting curve of K ED is smaller than that of K E, indicating that the bursting liability calculated by K E is strengthened. (5) PFC2D simulation shows that K ED decreases with increasing number of drilling hole in the coal component. When using K ED to evaluate the bursting liability of coal–rock combination, it is more reasonable and applicable.